Experiences of university employees of the impact of a mindful self-care and resiliency program on their well-being. Issue 3 (16th April 2021) - Hegney, Desley; Tsai, Lily; Craigie, Mark; Crawford, Christopher; Jay, Sarah; Rees, Clare
ABSTRACT: University employees experience high levels of workplace stress, with the perception that it is increasing, due to less autonomy, increased student numbers, excessive administrative work and role ambiguity. This study is part of a larger evaluation of the effectiveness of a Mindfulness, Self-Care and Resiliency (MSCR) program to improve the well-being of university employees in a regional university in Australia. In this study we report the results of interviews with 19 university employees who completed the program in 2019. The aim was to determine the acceptability, feasibility, and sustainability of the program in a university setting. MSCR teaches resiliency skills to improve overall stress management, well-being, and self-care behaviour. The program was delivered to both academic and support (professional) staff. Of the 19 employees interviewed, 13 were academic and 6 were professional staff. As it was evident that there was no difference in emerging themes between the two groups, the data were pooled for thematic analysis. Two overarching themes were found: impact of the program on the individual self (pre-existing mindset and learning and the impact of the program on individual well-being and self-care) and the way the individual interacted with others in their environment (inside the work environment – physical space, interaction with others [staff and students]), attending follow-ups at work and outside the work environment (interaction with immediate family, social support). It is apparent that the program was acceptable, feasible and sustainable, with employees reporting changes from the program at the one-month interview point. Results highlight the importance of skills to build inner-calm to manage the complex work environment as well as providing permission to staff to implement self-care activities in the workplace, regardless of their employment status.